The great ghost hoax - Ecton, Emily (Ecton, Emily. Great pet heist, 2021)
When Mrs. Third Floor visits and reports paranormal activity on the fifth floor, Butterbean and the other pets set out to find the truth and save Mrs. Third Floor from being scammed by professional ghost hunters.